Copine 7 promotes colorectal cancer proliferation through PKM2 interaction and MAPK signaling pathway - Yu, Tianwen; Huang, Changhao; Lai, Chen; He, Qing; Yuan, Weijie; Chen, Zihua (Frontiers in Oncology, 2023)
Introduction Colorectal cancer (CRC) is currently the third most common cancer in the world, and its prevalence and mortality rate continue to increase. Methods Based on an analysis of The Cancer Genome Atlas database, Tumor Immune Estimation Resource and Gene Expression Profiling Interactive Analysis, we explored the expression of CPNE7 in tumors. Immunohistochemistry and quantitative polymerase chain reaction analysis the expression of CPNE7 in colorectal cancer. Our study explored how CPNE7 promotes CRC cell proliferation and migration in vitro and in vivo. Transcriptome sequencing and Co-IP assay explored the underlying mechinaism of CPNE7 founction. Results We found the CPNE7 was overexpressed in CRC by database and IHC. CPNE7 promoted CRC cells proliferstion and migration in vitro and in vivo. Comparing and analyzing transcriptome sequencing between exogenous up-/downregulated CPNE7 CRC cells and the controls, we found that CPNE7 activates mitogen-activated protein kinase (MAPK) signaling pathway stimulating cancer cell proliferation. Coimmunoprecipitation experiments revealed an interaction between CPNE7 and pyruvate kinase muscle protein (PKM2). We also found the activity of MAPK signaling is regulated by exogenous CPNE7 expression. Discussion These results imply that CPNE7 may promote the progression of CRC by interacting with PKM2 and initiating the MAPK signaling pathway.